Cyanidin-3-O-Glucoside improves the viability of human islet cells treated with amylin or Aβ1-42 in vitro. - Jennifer Croden (Public Library of Science (PLoS), 2021)
Islet transplantation is being considered as an alternative treatment for type 1 diabetes. Despite recent progress, transplant recipients continue to experience progressive loss of insulin independence. Cyanidin-3-O-Glucoside (C3G) has shown to be protective against damage that may lead to post-transplant islet loss. In this study, human islets cultured with or without C3G were treated with human amylin, Aβ1-42, H2O2, or rapamycin to mimic stresses encountered in the post-transplant environment. Samples of these islets were collected and assayed to determine C3G's effect on cell viability and function, reactive oxygen species (ROS), oxidative stress, amyloid formation, and the presence of inflammatory as well as autophagic markers. C3G treatment of human islets exposed to either amylin or Aβ1-42 increased cell viability (p<0.01) and inhibited amyloid formation (p<0.01). A reduction in ROS and an increase in HO-1 gene expression as well as in vitro islet function were also observed in C3G-treated islets exposed to amylin or Aβ1-42, although not significantly. Additionally, treatment with C3G resulted in a significant reduction in the protein expression of inflammatory markers IL-1β and NLRP3 (p<0.01) as well as an increase in LC3 autophagic marker (p<0.05) in human islets treated with amylin, Aβ1-42, rapamycin, or H2O2. Thus, C3G appears to have a multi-faceted protective effect on human islets in vitro, possibly through its anti-oxidant property and alteration of inflammatory as well as autophagic pathways.